2016
DOI: 10.1161/atvbaha.116.307715
|View full text |Cite
|
Sign up to set email alerts
|

Osteoclastogenic Differentiation of Macrophages in the Development of Abdominal Aortic Aneurysms

Abstract: Objective-Arterial calcification is common and contributes to the pathogenesis of occlusive vascular disease. Similar to the dynamics of bone, it is a tightly controlled process that maintains a balance between osteogenesis and osteolysis. However, whether calcium homeostasis plays a role in the development of aneurysms has not been explored. We hypothesized that macrophages differentiate into osteoclasts in aneurysmal arteries and that protease byproducts contribute to aneurysm pathophysiology. Approach and R… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
48
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 35 publications
(52 citation statements)
references
References 38 publications
4
48
0
Order By: Relevance
“…Some investigators further revealed a differential mRNA and protein expression of MMP9 between M1 and M2 macrophages within the aneurysmal wall, suggesting that macrophages may differentially regulate ECM degradation depending on their phenotype and activation profile 47 . Another study identified macrophages positive for osteoclast markers in human aneurysmal aortas, and revealed higher protease activity in these cells compared to undifferentiated macrophages 102…”
Section: Ecm Remodeling Results From a Balance Between The Activitiesmentioning
confidence: 98%
“…Some investigators further revealed a differential mRNA and protein expression of MMP9 between M1 and M2 macrophages within the aneurysmal wall, suggesting that macrophages may differentially regulate ECM degradation depending on their phenotype and activation profile 47 . Another study identified macrophages positive for osteoclast markers in human aneurysmal aortas, and revealed higher protease activity in these cells compared to undifferentiated macrophages 102…”
Section: Ecm Remodeling Results From a Balance Between The Activitiesmentioning
confidence: 98%
“…91 Their recent study has also provided evidence that calcification is present in human AAA, and pharmacological inhibition of osteoclastogenesis prevents the development of calcium phosphate-induced AAA in mice. 92 …”
Section: Abdominal Aortic Aneurysmsmentioning
confidence: 99%
“…This finding was initially unexpected and surprising, but it is possible that MMP‐9 may mediate vascular calcification through several possible molecular mechanisms . First, it has been reported that apoptotic macrophages in the lesions can release microcalcification‐generating matrix vesicles into the ECM, eventually resulting in calcification which is supported by our finding that macrophage‐rich lesions contained microcalcification. High expression of caspase‐3 in the lesions of Tg rabbits allowed us to speculate that increased cell death may be also involved in the process of vascular calcification.…”
Section: Discussionmentioning
confidence: 99%